SISTEM PERILAKU LINGKUNGAN DI MALALAYANG BEACH WALK KOTA MANADO - Salangka, Cindy Ribka; Waani, Judy O; Wuisang, Cynthia E V (Universitas Bina Taruna Gorontalo, 2025)
The discussion of this research aims to understand the environmental behavior system based on behavioral attributes according to the theory proposed by Weisman (1981) that appears in its interaction with the environment so that it can become the basis for an assessment that the public open space can accommodate all functions or user activities. This research uses qualitative research methods with behavior mapping data collection methods consisting of place-centered mapping, person-centered mapping and physical trace behavior mapping methods to obtain information about emerging behavioral attributes. From the observation of 106 people, five dominant attributes emerged, namely, comfort, sociality, visibility, accessibility, and adaptability. However, there are shortcomings in meeting the needs of visitors based on these five attributes. The proposed design direction can maximize the function of Malalayang Beach Walk Manado City as a public open space that can accommodate a variety of user activities. Understanding the influence of user behavior on the environment can provide a perspective in developing a more comfortable and sustainable space.